Dental arch relationship in Bangladesh children with non-syndromic unilateral cleft lip and palate(UCLP) - Haque, Sanjida (2016)
Cleft lip and palate (CLP) is one of the most common birth defects. Multiple factors are believed to be responsible for an unfavorable dental arch relationship (DAR) in CLP. Facial growth (maxillary) retardation, which results in class III malocclusion, is the primary challenge that CLP patients face. Congenital factors (UCLP type, UCLP side, family history of cleft, family history of class III) and postnatal treatment factors (cheiloplasty, palatoplasty) may influence treatment outcomes in unilateral cleft lip and palate (UCLP) children, which has led to a great diversity in protocols and surgical techniques by various cleft groups worldwide. The aim of this retrospective study was to evaluate DAR of non syndromic Bangladeshi UCLP children and to explore the various congenital and postnatal treatment factors that are responsible for unfavorable DAR. Eighty four dental models were taken before orthodontic treatment and alveolar bone grafting. The mean age was 7.69± 2.46 (mean± SD). All the subjects had primary surgery (cheiloplasty and palatoplasty) at the same hospital. DAR was assessed blindly by five raters using GOSLON Yardstick (GY) and EUROCRAN index (EI) and by two raters using modified Huddart Bodenham (mHB) scoring system. Furthermore, all the subjects were divided into two groups; favorable and unfavorable groups. This grouping was carried out because patients in the favorable groups may not need further treatment after palatoplasty or cheiloplasty or they could be treated with conventional orthodontics, whereas patients in the unfavorable groups sometimes required surgical correction. Kappa statistics was used to evaluate the intra- and interexaminer agreements, chi square was used to assess the associations and logistic regression analysis was used to explore the responsible factors that affect DAR. Total 37 subjects (44% of all subjects) were categorized into unfavourable group (category rating 4 and 5) using GY.The mean GOSLON score was 3.238. Intra- and inter-examiner agreements were very good. Using crude and stepwise backward regression analysis, significant association was found between family history of skeletal class III malocclusion (p = 0.015 and p = 0.014 respectively) and unfavourable DAR. Complete UCLP (p = 0.054) and left sided UCLP (p = 0.053) also seemed to be correlated with unfavourable DAR using crude and stepwise backward regression analysis respectively but no significant associations was found. Total 47 subjects (56% of all subjects) were categorized into unfavourable group (category rating 3 and 4) using EI. The mean EUROCRAN scores were 2.44 and 1.93 for DAR and palatal morphology (PM) respectively. Intra- and inter-examiner agreement was good to very good. Using crude and stepwise backward regression analyses, significant associations were found between the modified Millard technique (p = 0.047, p = 0.034 respectively) of cheiloplasty and unfavorable DAR. Complete UCLP (p = 0.017) was also significantly correlated with unfavorable DAR. The PM showed a significant association with the type of cleft, type of cheiloplasty and type of palatoplasty. Total 39 subjects (46% of all subjects) were categorized into unfavourable group (category ratings poor and very poor) using mHB scoring system. The total mHB score was -8.26. Intra- and inter-agreement was very good. Using crude and stepwise backward regression analysis, significant association was found between positive history of class III (p = 0.025, p = 0.030 respectively) and unfavorable DAR. Using chi square test, complete UCLP (p = 0.003) and V-Y pushback palatoplasty (p = 0.005) were also significantly correlated with unfavorable DAR. This multivariate study suggested that DAR of non syndromic Bangladeshi UCLP children was significantly correlated with some of congenital and postnatal treatment factors by using different indices.